2023
DOI: 10.3390/drones7050322
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Autonomous UAV Networks: A Survey

Abstract: Recent advancements in unmanned aerial vehicles (UAVs) have proven UAVs to be an inevitable part of future networking and communications systems. While many researchers have proposed UAV-assisted solutions for improving traditional network performance by extending coverage and capacity, an in-depth study on aspects of artificial intelligence-based autonomous UAV network design has not been fully explored yet. The objective of this paper is to present a comprehensive survey of AI-based autonomous UAV networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…The works of [20] and [23] utilized AI-aided solutions for better beyond 5G generation by discovering that the ML-based paradigm enables cost-effective UAV network deployment through resource management, routing, and access protocols. Different AI systems were presented within three classification schemes: applications, algorithms, and training [25].…”
Section: A Existing Surveymentioning
confidence: 99%
“…The works of [20] and [23] utilized AI-aided solutions for better beyond 5G generation by discovering that the ML-based paradigm enables cost-effective UAV network deployment through resource management, routing, and access protocols. Different AI systems were presented within three classification schemes: applications, algorithms, and training [25].…”
Section: A Existing Surveymentioning
confidence: 99%
“…A review and analysis of the literature on UAV networks has shown that AI-based UAVs are a technologically feasible and economically viable paradigm for the cost-effective design and deployment of such next-generation autonomous networks. This article identifies open research challenges in the emerging field of UAV networks [7]. Yograj Singh Mandloi & Yoshinobu Inada's research focuses on applying machine learning and neural networks to select actions and better understand the environment to control unmanned aerial vehicles, rather than using explicit models to achieve the same goal.…”
Section: Analysis Of the Latest Research And Publicationsmentioning
confidence: 99%
“…Methods for improving and implementing innovative technologies in UAVs' collective selforganisation systems have been studied by domestic and foreign scientists relatively recently [5,7,10,11]. Numerous scientific articles propose solutions to problematic issues in the field of AI application in UAV control systems, building a control system based on various systems and platforms, for example, using multiagent systems.…”
Section: The Solutionmentioning
confidence: 99%
“…From another perspective, AI allows for automatic feature extraction while better managing onboard resources, which differentiates it from traditional cognitive algorithms [103]. Concerning UAV navigation, AI algorithms are characterized in this manuscript according to their paradigm as follows: AI algorithms that involve mathematical model formulation to find the best solution to a given problem by relying on predefined rules and objectives to guide the UAV are grouped in the first set (i.e., mathematical optimization) [104]. The other set emphasizes a paradigm that trains the models to make better decisions in UAV navigation (i.e., performance is evolved over time based on training data and gained experience) [105].…”
Section: Strategy (A) Vision-based Techniquesmentioning
confidence: 99%